Treatment outcomes in Wilms tumor (Colombia Medica, 1992)
Nephroblastoma (Wilms'tumor) is a common neoplasia in children, in which there have been major advances in its treatment. Results obtained at the Hopsital Universitario del Valle, Cali, Colombia from 1978 to 1988 (60 patients), are given. Demographic findings were similar to those reported elsewhere, with similar figures in boys and girls, with an average age of 3.3 years at presentation, but a little higher in boys (range newborns to 7 years). Of all the patients, 15 were stage I, 13, stage II, 17, stage III, 10, stage IV, and 5, stage V, with favorable histology in most of them. Despite the great number of children with stages III and IV (45%) and of 13 that abandoned the treatment, results were very good, with 30 patients cured (50%), which means a " corrected" cure rate of 64% (30 out of 47 that had completed treatment). The "corrected" percentages of cure were very similar to those of the National Wilms' Tumor Study (NWTS) of the United States, which means 87.6%, 100%, and 60% for stages I, II, and III, respectively. The above-mentioned results are encouraging and should foster the treatment of this and other neoplastic diseases, hopefully within national cooperative groups.